O cuidado em saúde: das produções em serviço social à prática profissional do assistente social - Martins, Gisele Justiniano de Faria (2021)
The investigation of health care in professional practice by social workers is the focus of this research. And based on the assumption that care does not present itself as a privileged dimension of the work of the social worker in the provision of services in the health area and among the protective policies and knowledge that involve this activity that we had as objective to analyze the practice of care in the professional practice of the social worker in the municipality of Goiânia-Go. The data of this study were produced through qualitative, analytical and investigative research of social reality, through bibliographic and documentary research based on health care in the professional practice. Thus, the field research was carried out at the Dona Iris Hospital and Maternity In the city of Goiânia- Go, with professionals who compose social work and some who work in this hospital in the area of care. Then, 09 interviews were conducted, using the technique of content analysis by the following axes: identification of health professionals; professional daily life; activities and demands; conceptions and meanings of care; manifestations and recognitions of families and trends in care in Social Work. However, the research demonstrated that care in professional practice is present since the user's arrival at the institution and the professional must have an expanded look going in addition to the provision of services. And it brought some trends of care manifested in the narratives of social workers such as: social right, protection of life, mediation in access to services